2017
DOI: 10.5590/jerap.2017.07.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development and Educational Policy: A Comparison of Two Fields in Education

Abstract: The purpose of this paper is to compare two fields of research related to school reform: professional development and educational policy. A content analysis of the literature in both fields revealed two areas where they align (i.e., a focus on teachers' professional development and the idea that change takes time) as well as two areas where there are differences (i.e., theoretical grounding of each field and planning for teachers' learning). Considerations for successful school reform are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…When faculty concerns are heard in a safe and trusting environment, teachers are more willing to identify the problem and play an important role in mitigating a solution in conjunction with education leaders (Massachusetts Department of Elementary and Secondary Education [MDESE], 2015). Professional development and training centered on ethical decision-making and situational awareness is a means to enact empowerment of faculty leading to enhanced efficacy (Martin et al, 2017;Yoo, 2016). Education leaders seeking to develop a school vision of learning are aware that a school culture supporting this vision is constructed of a set of "behavioral norms that exemplify the best that a school stands for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When faculty concerns are heard in a safe and trusting environment, teachers are more willing to identify the problem and play an important role in mitigating a solution in conjunction with education leaders (Massachusetts Department of Elementary and Secondary Education [MDESE], 2015). Professional development and training centered on ethical decision-making and situational awareness is a means to enact empowerment of faculty leading to enhanced efficacy (Martin et al, 2017;Yoo, 2016). Education leaders seeking to develop a school vision of learning are aware that a school culture supporting this vision is constructed of a set of "behavioral norms that exemplify the best that a school stands for.…”
Section: Discussionmentioning
confidence: 99%
“…By observing and reflecting on the practices of faculty at their school site, education leaders were empathetic to ethical decision-making processes. Additionally, the education leaders were able to gain a deeper understanding of how to generate innovative systemic change within their schools and empower faculty to take ownership (Hartman et al, 2017;Martin et al, 2017) to create an ethical, safe, and healthy working and learning environment (Carmel-Gilfilen & Portillo, 2016;Kolko, 2010). Campbell (2003) explored the ties of ethics to education on topics within the teaching profession, specifically learning to create an ethical culture and applied knowledge of ethics within the classroom and school community.…”
Section: Purposementioning
confidence: 99%
“…According to the analysis of scientific literature (Chu et al, 2016, Kurliand et al, 2005, Martin et al, 2017, Yahupov, 2007, we have found that the category «quality» refers to a subject or individual receiving personal orientation and to a person's readiness, capacity and aptitude to a certain activity. In this case, quality is an integral characteristic whose basic components are its characteristics manifestations.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The teacher educators had contextualized experiences of the need for teachers so that the educational policy became adaptable to the teachers and conceptualized necessary aspects for professional growth of the teachers. Martin, Kragler, and Frazier (2017) mention that there is an interconnection in purpose between educational policy and teacher's professional development, that is to sustain quality education in school. They further discuss the result of educational policy that…”
Section: Educational Policy and Teacher's Professionalismmentioning
confidence: 99%